1978
DOI: 10.1073/pnas.75.10.4819
|View full text |Cite
|
Sign up to set email alerts
|

Specific transcription of eukaryotic tRNA genes in Xenopus germinal vesicle extracts.

Abstract: Cloned tRNA genes from Drosophila and from yeast have been transcribed faithfully in extracts prepared from Xenopus germinal vesicles. The newly formed RNA is composed of precursor tRNAs (of 5S RNA size and of tRNAs. The plasmid pCIT12 carries genes for Drosophila tRNALYS, tRNAg, and tRNA1sn. Nucleotide analysis of one RNA species transcribed from pCIT12 DNA showed it to be identical to Drosophila tRNALYS; it even contained some of the modified nucleotides expected for this tRNA. This RNA species is formed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Of the alcohol-soluble radioactivity released by the cytoplasmic enzyme, 90% was in the form of a mononucleotide since it could be converted to uridine by alkaline phosphatase. In contrast, only 22 and 10% of the radioactivity released by the high-and low-molecular-weight nuclear enzymes, respectively, were mononucleotide. These results suggest that the cytoplasmic activity is primarily exonucleolytic and the nuclear activities primarily endonucleolytic, although the higher-molecular-weight nuclear enzyme is probably contaminated with some exonuclease.…”
mentioning
confidence: 98%
“…Of the alcohol-soluble radioactivity released by the cytoplasmic enzyme, 90% was in the form of a mononucleotide since it could be converted to uridine by alkaline phosphatase. In contrast, only 22 and 10% of the radioactivity released by the high-and low-molecular-weight nuclear enzymes, respectively, were mononucleotide. These results suggest that the cytoplasmic activity is primarily exonucleolytic and the nuclear activities primarily endonucleolytic, although the higher-molecular-weight nuclear enzyme is probably contaminated with some exonuclease.…”
mentioning
confidence: 98%
“…To find out if our gene could be actively transcribed by RNA polymerase I11 in vitro, we performed transcription experiments using a nuclear extract prepared from germinal vesicles isolated from Xenopus laevis oocytes [39] and cytoplasmic extracts prepared from HeLa cells [40]. While the HeLa cell extract cannot initiate transcription of our plasmid, transcription products can be observed using a germinal vesicle extract (Fig.…”
Section: Transcription Experiments In Vitromentioning
confidence: 99%
“…Transcription in vitro 0.5 pg plasmid DNA was used as a template for RNApolymerase-111-directed transcription either in extracts prepared from Xenopus laevis germinal vesicles [39] or from HeLa cells [40]. Transcription reactions, using a germinal vesicle extract, contained per 20 pl: 0.5 mM ATP, CTP and UTP, 0.05 mM GTP, 3 pCi [ce3'P]GTP (635 Ci/mmol), 0.5 mM dithiothreitol, 70mM KC1, 7 mM MgCI2, 10 mM Hepes pH 7.4 and extract prepared from 10 germinal vesicles.…”
Section: Construction Of Deletion Clones By Bal 31 Digestionmentioning
confidence: 99%
“…Investigations into the expression of tRNA genes of yeast (10,11), Xenopus (12), and DrosophiZa (13) have demonstrated that in vivo and in vitro analysis of eukaryotic precursor tRNAs is now feasible. These studies require the knowledge of the nucleotide sequence of the specific mature tRNAs.…”
Section: Introductionmentioning
confidence: 99%